The Edukasi Penggunaan Obat Tradisional Halal bagi Ibu Rumah Tangga: Integrasi Iman dan Ilmu Farmasi - Ahmad Suryadi (PENDIMAS: Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to improve health literacy and housewives' understanding of the use of halal traditional medicines through the integration of faith and pharmaceutical science. The problem faced by partners is the low level of knowledge regarding the safety, halal status, and legality of traditional medicines that are widely circulating in the community. The activity was carried out through educational workshops using the Participatory Action Research method and the Asset-Based Community Development approach, including material delivery, practical demonstrations, interactive discussions, and pre-test and post-test evaluations. The results of the activity showed a significant increase in participants' knowledge regarding the identification of halal traditional medicines, the principles of phytotherapy safety, and skills in selecting and processing herbal ingredients hygienically. Participants also demonstrated positive attitude changes in integrating religious values with family health practices. This program promotes family autonomy in maintaining health through the use of safe halal herbs and can be replicated in other communities to enhance public health literacy.